Optimization of internal mixing parameter on the electrical conductivity of multiwall carbon nanotubes/synthetic graphite/epoxy nanocomposites for conductive polymer composites using Taguchi method - Irmayani,; Suherman, Hendra (Penerbit Universiti Kebangsaan Malaysia, 2017)
Conductive polymer composites (CPCs) can be widely uses as electronic devices, artificial muscles, solar energy conversion, and sensors. Nevertheless, CPCs has a low electrical conductivity. Therefore this study focused to improved the electrical conductivity of CPCs by optimizing the internal mixing parameter using Taguchi Method. Multiwall carbon nanotubes (MWCNTs) as secondary filler and synthetic graphite (SG) as primary filler use in this study. The CPCs composition are; 5 wt% MWCNTs; 75 wt% SG; 20 wt% epoxy resin as matrix. The internal mixing parameter applied as control factor in Taguchi Method analysis are mixing time, mixing temperature, and mixing rotation. Experiment was carried out based on orthogonal array design using these three internal mixing parameter. The results were analyzed using the signal to noise ratio (S/N) and analysis of variance (ANOVA). The percent contribution of each internal mixing parameters to the electrical conductivity of MWCNTs/SG/epoxy resin were mixing rotation (44%), mixing temperature (26%) and mixing time (18%). This was managed to reduce the number of voids and nano size particles conductive filler material (MWCNTs) more evenly dispersed in the epoxy resin. The optimum internal mixing parameters used to produce MWCNTs/SG/epoxy nanocomposites was effective to increase the electrical conductivity becomes 197 S/cm.